The Semenyih by-election: survey findings on voters and issues - Syed Abdullah Idid, Syed Arabi; Zulkifli, Khairul Syakirin (2019)
The outcome of the Semenyih By-Election raised several questions on the strength of the political parties post General Election 14. The by-election was important for several reasons, among them was that it was contested in a Malay majority area amidst the growing movement of an UMNO-PAS cooperation to deny PH victory in the area of immediate consequence but also in the other constituencies, if the co-operation were proven to be successful. This paper will offer a brief analysis and provide findings on a study made before and after the by-election. Two face-to-face interviews conducted on more than 900 voters identified the issues of importance to them and the basis in which decisions were made in choosing their party and candidate. The study found that there was a swing of the young and elderly voters and candidate choice had some influence on the voting. The cooperation of PAS and BN boosted the performance for a win of the BN candidate in Semenyih. Issues played a part in favour of Pakatan Harapan but it was not fully utilized to their advantage.